2019
DOI: 10.3390/antiox8080274
|View full text |Cite
|
Sign up to set email alerts
|

HPLC-ESI-qTOF-MS/MS Characterization, Antioxidant Activities and Inhibitory Ability of Digestive Enzymes with Molecular Docking Analysis of Various Parts of Raspberry (Rubus ideaus L.)

Abstract: The anti-oxidative phenolic compounds in plant extracts possess multiple pharmacological functions. However, the phenolic characterization and in vitro bio-activities in various parts of raspberry (Rubus idaeus L.) have not been investigated systematically. In the present study, the phenolic profiles of leaves (LE), fruit pulp (FPE), and seed extracts (SE) in raspberry were analyzed by HR-HPLC-ESI-qTOF-MS/MS method, and their antioxidant activities and digestive enzymes inhibitory abilities were also investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(51 citation statements)
references
References 38 publications
2
49
0
Order By: Relevance
“…It was found that Glu 411 bound with each of the four phenolics, implying that it may exert important functions in the catalytic reaction of α-glucosidase. Many studies also verified that Asp 215 and Glu 411 were the important active sites involved in this catalytic reaction [28,34]. In addition, the formation of hydrogen bonds between the hydroxyl group at C-3 or C-4 of the molecules (i.e., quercetin and rutin) and the active site residues may produce a higher inhibitory ability towards α-glucosidase compared to kaempferol-3-O-rutinoside, which was consistent with the results reported by Zeng et al (2016) [41].…”
Section: Molecular Docking Analysismentioning
confidence: 80%
See 1 more Smart Citation
“…It was found that Glu 411 bound with each of the four phenolics, implying that it may exert important functions in the catalytic reaction of α-glucosidase. Many studies also verified that Asp 215 and Glu 411 were the important active sites involved in this catalytic reaction [28,34]. In addition, the formation of hydrogen bonds between the hydroxyl group at C-3 or C-4 of the molecules (i.e., quercetin and rutin) and the active site residues may produce a higher inhibitory ability towards α-glucosidase compared to kaempferol-3-O-rutinoside, which was consistent with the results reported by Zeng et al (2016) [41].…”
Section: Molecular Docking Analysismentioning
confidence: 80%
“…It is worth noting that little information was available regarding the structure of α-glucosidase from Saccharomyces cerevisiae. Hence, its homologous structure (isomaltase, PDB ID: 3A4A) obtained from RCSB PDB was usually applied to conduct the docking test [27,28]. The Surflex-Dock Geom (SFXC) mode was used to perform docking analysis using SYBYL-X 2.0 software (Tripos, Inc., St. Louis, MO, USA).…”
Section: Molecular Docking Analysismentioning
confidence: 99%
“…However, synergistic effects with other flavonoids could enhance inhibitory activities. The mechanism by which phenolic compounds inhibit digestive enzymes are attributed with their binding to amino acid residues at enzyme active sites via hydrogen bonding, thereby inhibiting the catalytic reaction of enzymes [ 28 , 29 , 30 ]. Results from this work indicate that decorticated sorghum grains contain substantial flavonoids which could retard carbohydrate hydrolyzing enzymes and thus help ameliorate diabetes and its associated diseases.…”
Section: Resultsmentioning
confidence: 99%
“…Inhibition analysis of α-amylase activity was conducted in order to corroborate the potential antihyperglycemic activity of phenolic compounds contained in passiflora passion fruit extracts. As reported by several authors [50,51], the inhibition of some key digestive enzymes, such as α-amylase, is a good strategy to treat or inhibit hyperglycemia. The highest α-amylase inhibition shown by the FPC extract could be justified by the higher content of phenolic compounds compared to the BPC extract.…”
Section: Discussionmentioning
confidence: 98%